Muslim Persecution of Heretics during the Marwānid Period (64–132/684–750) - Judd, Steven (Al-Masaq: Journal of the Medieval Mediterranean, 2011)
This article traces the emergence of a systematic approach to combating heresy during the Umayyad period. It argues that the Umayyads sought to silence religious dissent by labelling it as heresy and that the doctrinal boundaries of orthodoxy narrowed as the Umayyad period progressed. The article also asserts that Umayyad efforts to impose their vision of orthodoxy were an important precedent for the mihna under the Abbasids. © 2011 Society for the Medieval Mediterranean.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/146-546-256-080-649 tex.type: [object Object]
Keywords: Abd al-Malik; Ghaylan al-Dimashqi; Heretic; Hisham; Islam - heresy; Islamic scholar; Mabad al-Juhani; Qadariyya; Theological movement; Ummayad caliph; Ummayad caliphate; dept.his